The Dispute Resolution Revolution: A Civil Law Analysis of Online Dispute Resolution (ODR) Mechanisms - Hendri Khuan; Achmad Fitrian; Loso Judijanto; Herry M Polontoh (Ipso Jure, 2025)
The development of information technology and digitalization has encouraged the emergence of Online Dispute Resolution (ODR) as an alternative dispute resolution that is more efficient and adaptive to the dynamics of electronic transactions. ODR, supported by Law No. 11/2008 on Electronic Information and Transactions (ITE Law) and its amendments, offers a faster and more affordable solution than traditional mechanisms such as litigation or arbitration. However, the implementation of ODR in Indonesia still faces significant challenges, including the lack of clear regulations regarding the recognition and execution of judgments, as well as the protection of personal data. The ITE Law provides a legal foundation for electronic transactions, but further adjustments are needed to ensure ODR can be legally recognized and accounted for, especially in the context of cross-border disputes. In addition, aspects of transparency, accountability, and data security must be prioritized in the implementation of ODR. This research uses a normative juridical method to analyze the application of ODR in the Indonesian civil law system, assess the suitability of existing regulations, and identify challenges and opportunities faced. Comprehensive regulatory harmonization is needed to ensure ODR can function effectively, fairly, and safely for all parties, and become an integral part of a more modern and relevant Indonesian legal system in the digital era.